Optimization of nitration steel 38ХМЮА in glow discharge to the parameter in the melt durability glass filled plastics - Каплун, В.Г.; Матвіїшин, П.В.; Машовець, Н.С. (Problems of Tribology, 2014)
The results of experimental studies of wear resistance of steel samples in the field 38HMYUA Glass filled with molten plastic PS68-30, which strengthened by nitriding in glow discharge in a medium mixture of nitrogen with argon for different technological regimes. The optimum nitriding treatment that provides maximum durability in this field has been stated